Indian Civilization Influence of Islam during Delhi Sultnat Period: The Impact of Islam on Indian Civilization during the Delhi Sultanate Period (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper describes the civilization position of Islam as having an effect on the political structure, organization and culture of native Indian communities, including the majority of Buddhist Hindu cultures within the Delhi Sultanate territorial boundaries. Kabir was the most influential person of all. Islamic art, sculpture and craftsmanship had a certain originality that enriched the fabric of Indian society. The civilization influence of Islam could be narrowly separated into two interlinked categories the early Arab-Islamic, Umayyad or Abbasid ages in West Asia as well as the latter era of the Delhi Sultanate, marked primarily by Turkish and Afghan administrators from Central Asia or Pakistan.